Role of the RNA-binding protein La in cancer pathobiology - Sommer, Gunhild (RNA Biol, 2020)
RNA-binding proteins are important regulators of RNA metabolism and are of critical importance in all steps of the gene expression cascade. The role of aberrantly expressed RBPs in human disease is an exciting research field and the potential application of RBPs as a therapeutic target or a diagnostic marker represents a fast-growing area of research. Aberrant overexpression of the human RNA-binding protein La has been found in various cancer entities including lung, cervical, head and neck, and chronic myelogenous leukaemia. Cancer-associated La protein supports tumour-promoting processes such as proliferation, mobility, invasiveness and tumour growth. Moreover, the La protein maintains the survival of cancer cells by supporting an anti-apoptotic state that may cause resistance to chemotherapeutic therapy. The human La protein represents a multifunctional post-translationally modified RNA-binding protein with RNA chaperone activity that promotes processing of non-coding precursor RNAs but also stimulates the translation of selective messenger RNAs encoding tumour-promoting and anti-apoptotic factors. In our model, La facilitates the expression of those factors and helps cancer cells to cope with cellular stress. In contrast to oncogenes, able to initiate tumorigenesis, we postulate that the aberrantly elevated expression of the human La protein contributes to the non-oncogenic addiction of cancer cells. In this review, we summarize the current understanding about the implications of the RNA-binding protein La in cancer progression and therapeutic resistance. The concept of exploiting the RBP La as a cancer drug target will be discussed.